RANCANG BANGUN ALAT AUTO FEEDER HEWAN PELIHARAN BERBASIS ARDUINO - Eko, Eko Giri Pratama; Hotma Pangaribuan (LPPM Universitas Putera Batam, 2025)
Ensuring proper and regular feeding is an important aspect of maintaining the health and well-being of pets. However, pet owners sometimes face challenges in consistently providing food to their pets, especially when they are busy with work or other activities. To address this issue, an automated feeding system can be an effective solution. This abstract highlights the implementation of an automated pet feeding system using Arduino Uno, a popular open-source microcontroller board. The system is designed to dispense the appropriate amount of food at scheduled times, ensuring that pets receive their meals on time. The Arduino Uno acts as the brain of the system, controlling various components such as a motorized food dispenser, a digital display for programming and monitoring, and sensors for detecting the presence of pets and food levels. By utilizing a programmable microcontroller, the system can be easily customized to accommodate specific feeding requirements and pet schedules. Overall, the automated pet feeding system using Arduino Uno offers a practical and reliable solution for pet owners who struggle to maintain consistent feeding routines. By utilizing technology such as Arduino Uno, pet owners can ensure that their pets receive proper nutrition, even in their absence.